2007
DOI: 10.1002/ejlt.200600079
|View full text |Cite
|
Sign up to set email alerts
|

Plastic fats and margarines through fractionation, blending and interesterification of milk fat

Abstract: Plastic fats and margarines through fractionation, blending and interesterification of milk fatMilk fat stearins and oleins were blended with high-and low-melting natural fats to produce plastic fats, vanaspati substitute and confectionery fats. Margarines of improved nutritional value were also formulated. Fractionation was carried out using acetone, hexane, and isopropyl alcohol. The yield (wt-%) of high-melting stearin (HMS) from acetone and IPA was 13.0 6 0.2 to 13.3 6 0.1 after crystallization for 24 h at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Abd ElAziz (2008) showed that the higher content of unsaturated fatty acids in the low-melting milk fat fractions was related directly to the oxidative instability. De et al (2007) reported that, in solvent crystallization, the crystallization temperature has to be much lower when non-polar solvents (e.g., hexane) are used, compared with polar ones (e.g., acetone, isopropanol). It was shown that, in all solvent systems used, the milk fat was readily fractionated into three fractions, with distinctive differences in their melting points (De et al, 2007).…”
Section: Fractionation Of Milk Fatmentioning
confidence: 99%
See 2 more Smart Citations
“…Abd ElAziz (2008) showed that the higher content of unsaturated fatty acids in the low-melting milk fat fractions was related directly to the oxidative instability. De et al (2007) reported that, in solvent crystallization, the crystallization temperature has to be much lower when non-polar solvents (e.g., hexane) are used, compared with polar ones (e.g., acetone, isopropanol). It was shown that, in all solvent systems used, the milk fat was readily fractionated into three fractions, with distinctive differences in their melting points (De et al, 2007).…”
Section: Fractionation Of Milk Fatmentioning
confidence: 99%
“…De et al (2007) reported that, in solvent crystallization, the crystallization temperature has to be much lower when non-polar solvents (e.g., hexane) are used, compared with polar ones (e.g., acetone, isopropanol). It was shown that, in all solvent systems used, the milk fat was readily fractionated into three fractions, with distinctive differences in their melting points (De et al, 2007). However, it should be noted that, while solvent crystallization is common practice in vegetable oil fractionation, the International Dairy Federation (IDF) does not support applying any kind of solvents for fractionation processes of milk fat (Illingfort, 2002).…”
Section: Fractionation Of Milk Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the diversity of fatty acids, milk fat has a very wide melting range (− 40 to 40°C) and is a very suitable material for physical fractionation which relies primarily on the melting points of the different TAG. Dry fractionation of AMF can produce a range of products with different physical and chemical characteristics, which are interesting for use as food ingredients, suitable for a wide range of applications (De et al, 2007). To further enhance the use of AMF or its fractions blended with vegetal fats in new mixedmargarines or shortenings (also called dairy blends), a better understanding of crystallization phenomena occurring between those lipids is required.…”
Section: Introductionmentioning
confidence: 99%
“…A gordura do leite interesterificada apresentou diminuição da consistência a 5 °C de 11152 para 2752 gf/cm 2 com a adição de 7,5% de óleo de girassol e 25% de ésteres de fitosteróis e para 1748 gf/cm 2 com a adição de 15% de óleo de girassol e 25% de ésteres de fitosteróis, evidenciando a capacidade da gordura do leite de acomodar diferentes quantidades de óleo sem modificar sua integridade estrutural, dependendo da quantidade dos outros componentes. 41 Mesmo havendo queda tão acentuada na consistência, estas misturas interesterificadas ainda apresentaram baixa plasticidade.…”
unclassified